The importance of the lesser-known Tongkat Ali Plants of Polyalthia bullata and Stema tuberosa for aging men - Fatinah, Ahmad; Sharifah Aminah, Tuan Said; Jaya Vejayan, Palliah (AIP Publishing, 2025)
Tongkat Ali, is a popular name in Malaysia and worldwide. Tongkat Ali is synonym to a number of plants traditionally used as aphrodisiacs. Other than the most popular Tongkat Ali plant of Eurycoma longifolia (or Tongkat Ali Putih), not known by many people are the two other Tongkat Ali plants of Stema tuberosa (Tongkat Ali Merah) and Polyalthia bullata (Tongkat Ali Hitam). Their names have been assigned due to their root colours, i.e. white, red and black. E. longifolia has been extensively sold and studied for its pharmacological activities, including aphrodisiac, antimalarial, anticancer, and antimicrobial properties. While the two lesser-known Tongkat Ali plants have not been well documented on their botanical features and pharmacological benefits, this review gives a comprehensive literature compilation to fill the knowledge gaps. All three types of Tongkat Ali plants claimed for many traditional uses and have been identified to exhibit pharmacological activities such as antimalarial, anticancer and antimicrobial activities. However, to date, their most distinctive pharmacological activities are their aphrodisiac capabilities due to their potential to boost testosterone. Testosterone, a crucial hormone for human health, is responsible for various bodily functions such as sexual performances, muscle mass, bone mass, and brain normalities. Treatments for low testosterone levels include testosterone replacement therapy, which if left uncontrolled can cause liver damage, jaundice, elevated hemoglobin levels, sleep apnea, and skin reactions. Some aging men experienced lower than normal serum testosterone levels and often resort to more natural testosterone boosters by consuming Tongkat Ali plants instead. This review emphasizes the values of S. tuberosa and P. bullata with scientific evidences as aphrodisiac plants worthy of being used similar to the more popular Tongkat Ali of E. longifolia.